2020
DOI: 10.1371/journal.pone.0236266
|View full text |Cite|
|
Sign up to set email alerts
|

Muscle strength, muscle power and body composition in college-aged young women and men with Generalized Joint Hypermobility

Abstract: The aim of this study was an evaluation of the musculoskeletal system in women and men with Generalized Joint Hypermobility (GJH). The study included 87 participants– 40 with Generalized Joint Hypermobility (aged 21.2 ±1.8 years) and 47 (aged 21.0 ±1.3 years) in the control group (CG). The study included the Beighton score, the measurements of body composition, muscle flexibility (Straight Leg Raise test, Popliteal Angle test, Modified Thomas Test), and the measurements of muscle strength and muscle power. T-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 49 publications
3
13
0
1
Order By: Relevance
“…This finding is consistent with previous research that found no relationship between hypermobility as assessed using the Beighton criteria and grip strength. 23 Research involving shoulder, hip and knee strength reports significantly reduced strength in hypermobile individuals in some aspects of strength, 9 , 10 , 11 , 12 , 13 although finding them equivalent with nonhypermobile counterparts when testing other aspects of strength. 10 , 11 , 12 , 13 In these studies and the present study, diagnosis of GJH was made using a score of 4 or more positive Beighton criteria, 10 , 11 , 12 but the studies varied between protocols and equipment used to measure strength.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is consistent with previous research that found no relationship between hypermobility as assessed using the Beighton criteria and grip strength. 23 Research involving shoulder, hip and knee strength reports significantly reduced strength in hypermobile individuals in some aspects of strength, 9 , 10 , 11 , 12 , 13 although finding them equivalent with nonhypermobile counterparts when testing other aspects of strength. 10 , 11 , 12 , 13 In these studies and the present study, diagnosis of GJH was made using a score of 4 or more positive Beighton criteria, 10 , 11 , 12 but the studies varied between protocols and equipment used to measure strength.…”
Section: Discussionmentioning
confidence: 99%
“…Research involving young adult populations reports lower strength in flexion and extension of the knee, shoulder, and elbow in participants with GJH, compared with age- and sex-matched controls. 9 , 10 , 11 , 12 , 13 Clinicians who believe that hypermobile athletes have less dynamic joint stability may prescribe strength training for their injury prevention and rehabilitation. 9 , 12 , 13 However, the same studies revealed that participants with GJH differences were equal to nonhypermobile counterparts in some aspects of strength testing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Generalized joint hypermobility is characterized by abnormal range of motion of systemic joints due to relaxation of surrounding ligaments and decreased muscle strength, which is mainly affected by their race, gender, and age, and is a connective tissue hereditary disease, in addition, periarticular ligament relaxation may eventually lead to the development of arthritic pairs. 1,27 It has been found that female patients have a higher degree of joint laxity than male patients, with a prevalence approximately three times that of male patients, 5,28,29 and the symptoms of laxity gradually decrease with age in male patients, while the joint laxity gradually increases with age after 15 years in female patients. 30 In females, hormones affect the extensibility of ligaments, and the phenomenon may be caused by hormonal changes that occur during puberty.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are no evidence-based strategies in the treatment of GJH. Case studies confirm the effectiveness of physiotherapeutic interventions in the treatment of GJH but leave many ambiguities [14].…”
Section: Introductionmentioning
confidence: 93%